Empathic Potential in Preschool Children with Mental Retardation - E.S. Ignatova; L.L. Ushakova; E.V. Kusheva (Клиническая и специальная психология)
The work is aims to study the features of empathic potential in children with mental retardation. The materials of empirical research obtained from a sample of preschool children are presented. The study involved respondents aged 5 to 6 years (N=32; M=5.19; SD=0.37) with an average level of intelligence. Pictures from the children's educational game “ABC of Emotions” (N.L. Belopolskaya), the drawing technique “Draw yourself”, the technique “Plot pictures” (R.R. Kalinina), the technique “Unfinished stories” (T.P. Gavrilova) and the Wexler’s test (children's version) were used. Mathematical processing methods include: χ2 (chi-squared) Pearson, Mann-Whitney U-test, cluster regression analysis. The results obtained make it possible to say that children with mental retardation do not differ from children without this status in terms of emotional awareness, the nature of emotional response and the moral component of empathic potential in general. At the same time, children with mental retardation find it difficult to choose the nature of their emotional response. This is a fact that can be used as a marker to determine the status of mental retardation. The results can be used in developing psychocorrection programs.